Relativistic quantum mechanics and quantum field theory - Devanathan, V (Alpha Science International, 2011)
Deals with the single particle relativistic wave equations and the elements of quantum field theory. In this book, how the quantum field theory is stretched beyond quantum electrodynamics to include electro weak interactions and strong interactions and how it leads to the formulation of the standard model of elementary particles are discussed.